Barriers to Long-Term Adherence in Botulinum Toxin Therapy for Post-Stroke Spasticity: Insights and Implications from a Single-Center Study in North Italy - Ester Cecchella; Nicola Luigi Bragazzi; Filippo Cotellessa; William Campanella; Luca Puce; Lucio Marinelli; Antonio Currà; Cristina Schenone; Laura Mori; Carlo Trompetto (Toxins)
Stroke is a leading cause of long-term disability worldwide, often resulting in spasticity. Botulinum toxin injections have emerged as a cornerstone in the management of post-stroke spasticity. However, despite their clinical efficacy, maintaining long-term adherence to botulinum toxin therapy remains a significant challenge. This retrospective observational study analyzed 106 patients undergoing botulinum toxin therapy for post-stroke spasticity to identify the key factors influencing treatment continuation. The mean age of the cohort at the time of stroke was 57.7 years, with ischemic strokes accounting for 61.3% of cases and hemorrhagic strokes for 38.7%. A total of 61.3% of patients continued therapy, while 38.7% discontinued therapy due to a variety of reasons. The most common reasons included logistical barriers (43.9%) and comorbidities (36.6%), followed by perceived lack of benefit (24.4%) and clinical resolution (12.2%). Among those citing a lack of benefit, muscular fibrosis was a notable contributor. In the multivariable Cox regression analysis, logistical challenges, such as access to healthcare facilities and administrative difficulties, were associated with discontinuation (HR = 13.95, 95% CI: 5.57–34.94, p < 0.001). Comorbidities also significantly increased the likelihood of discontinuation (HR = 3.51, 95% CI: 1.56–7.87, p = 0.002), as did the lack of benefit (HR = 14.34, 95% CI: 5.65–36.38, p < 0.001) and condition resolution (HR = 19.20, 95% CI: 5.58–66.02, p < 0.001). In contrast, demographic and clinical factors, including age at the time of stroke, gender, stroke type, affected side, and baseline spasticity severity, did not significantly influence treatment continuation. These findings underscore the importance of addressing logistical barriers and mitigating the burden of comorbidities to enhance treatment adherence. A shift toward patient-centered approaches that integrate robust rehabilitation services and streamline healthcare accessibility is critical for optimizing outcomes.